Biodiesel de buriti em trator: desempenho em função do tipo de diesel e da proporção de mistura na operação de preparo do solo - Iamaguti, Priscila Sawasaki [UNESP] (2014)
The biodiesel obtained from vegetable oils , animal fats or waste oils by reaction with ethanol or methanol, stands out among the renewable fuel supply while minimizing environmental problems . The aim of this study was to evaluate operating performance and smoke opacity of an agricultural tractor , using biodiesel as fuel ethanol buriti , interior diesel and diesel underground . The experiment was conducted in the Department of Agricultural Engineering , UNESP/Jaboticabal . The type B was S1800 diesel engine and S50, the proportions B0, B5, B15, B25, B50, B75 and B100 (where the number indicates the percentage of biodiesel in the diesel). Evaluated fuel consumption , power drawbar pull , speed actual displacement , power drawbar pull and smoke opacity. The results showed an increase of 5.41 % in specific fuel consumption compared with B100 B0 , however the type of diesel in the tractor performance variables. With respect to the opacity of the smoke , there was a reduction of 33.33 % and 28.90 % , respectively, with the increase of biodiesel in diesel indoor and underground